Mind Mapping Meets Classical Music: An Effective Strategy to Improve Chemistry Learning Achievement in Hydrocarbon Topic - Asep Sofyan; Moeketsi Freddie Tlali (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study is to evaluate the influence of using mind mapping learning accompanied by classical music on chemistry learning outcomes in the topic of hydrocarbon compounds among Class X students at State Senior High School 1 Tapung, Kampar. Methodology: This research uses an experimental method with a t-test design, where Class X-3 serves as the control group following conventional learning (teacher-centered), and Class X-5 serves as the experimental group using mind mapping learning accompanied by classical music. The data collection instruments consist of pre-test and post-test questions. Main Findings: The results of the descriptive analysis show that the experimental class, which used mind mapping accompanied by classical music, achieved higher learning outcomes compared to the control class that followed conventional learning methods. The results of the inferential analysis, using homogeneity and normality tests, indicate that the study hypothesis is accepted, showing a significant difference in student learning outcomes between the two groups. The t-test results reveal that tcount > ttable (3.43 > 1.61), with an effect size of 14%. The use of mind mapping learning accompanied by classical music significantly improves student learning outcomes on the topic of hydrocarbon compounds compared to conventional learning methods. Novelty/Originality of this study: This study provides a new contribution by proving that the use of mind mapping learning models combined with classical music can significantly improve student learning outcomes on hydrocarbon compound material compared to conventional learning.